Spatiality in a Virtual Classroom - Maharlika, Febry (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The spread of the COVID 19 virus has had a significant impact on the world of education. Concerns about the spread of the virus among academicians have caused system changes in teaching and learning activities. Online learning is an option for schools to keep teaching and learning activities running. This study describes the teacher's spatiality in teaching activities in virtual classes using the google meet video conference service. To illustrate this experience, a descriptive analysis research method is used by analyzing the virtual space spatial framework. The virtual space framework used as the reference for this study is the allocentric frame of reference, the egocentric frame of reference and the intrinsic frame of reference. The results of this study explain that there is a framework that shapes spatiality in online learning spaces. The spatiality that is formed is due to the relationship between objects, namely, teachers, students, computer screens with video conference services, forming spatiality based on the teacher's imagination, experience and knowledge.